2021
DOI: 10.1021/acsnano.0c10577
|View full text |Cite
|
Sign up to set email alerts
|

Superelastic, Hygroscopic, and Ionic Conducting Cellulose Nanofibril Monoliths by 3D Printing

Abstract: Compressible and superelastic 3D printed monoliths have shown great promise in various applications including energy storage, soft electronics, and sensors. Although such elastic monoliths have been constructed using some limited materials, most notably graphene, it has not yet been achieved in nature's most abundant material, cellulose, partly due to the strong hydrogen-bonding network within cellulose. Here, we report a 3D-printed cellulose nanofibril monolith that demonstrates superb elasticity (over 91% st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…Hence, inspired by natural plant transpiration, the methods to prepare similar porous structures are attractive, wherein water transports in the vertical aligned channels of the tree trunks with low flow resistance ( Tu et al, 2020 ). The porous structures of fibrous aerogels could be prepared by different methods, including plant templating, ice templating, foaming, and 3D printing, considering various strategies to improve the performance of SVG systems ( Zhang et al, 2005 ; Deville et al, 2006 ; Li et al, 2017c ; Shao et al, 2020 ; Chen et al, 2021b ).…”
Section: Pore Structures Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, inspired by natural plant transpiration, the methods to prepare similar porous structures are attractive, wherein water transports in the vertical aligned channels of the tree trunks with low flow resistance ( Tu et al, 2020 ). The porous structures of fibrous aerogels could be prepared by different methods, including plant templating, ice templating, foaming, and 3D printing, considering various strategies to improve the performance of SVG systems ( Zhang et al, 2005 ; Deville et al, 2006 ; Li et al, 2017c ; Shao et al, 2020 ; Chen et al, 2021b ).…”
Section: Pore Structures Constructionmentioning
confidence: 99%
“…Three dimensional metamaterials derived from 3D printing have gained growing popularity amid various approaches. The method known as direct ink writing is useful in printing diverse sophisticated structures using colloidal gel inks such as nanocellulose, graphene, CNTs, and polymers ( Chen et al, 2021b ). The ink could be directly assembled after being extruded by needle with designed structure, which relies on the rheological properties of materials.…”
Section: Pore Structures Constructionmentioning
confidence: 99%
“…Among them, ionic conductive cellulose hydrogels incorporated with inorganic salt ions gained considerable attention in the field of flexible energy storage devices due to their high ionic conductivity and good freezing tolerance 12 , 13 . However, since the salt ions can easily diffuse into the semicrystalline/crystalline regions of cellulose and weaken the hydrogen-bonding interaction between the cellulose chains, a trade-off between ionic conductivity and mechanical strength was frequently observed 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Barthelat and colleagues showed that GO membranes can be given complex shapes in the wet state by the use of 25% of cellulosic slurries of bres 50-2600 mm in length. 27 3D printing of CNF inks is a real possibility, 28 where it should be possible to include 2D nanosheets. For CNF-GO nanocomposites, there are not so many previous studies, [29][30][31][32] whereas graphene or reduced GO have been used more frequently 30,[33][34][35][36] when high electrical conductivity is desirable.…”
Section: Introductionmentioning
confidence: 99%